2011
DOI: 10.1158/0008-5472.can-10-1749
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Structural Variation in the Gastric Cancer Kinome Revealed through Targeted Deep Sequencing

Abstract: Genetic alterations in kinases have been linked to multiple human pathologies. To explore the landscape of kinase genetic variation in gastric cancer (GC), we used targeted, paired-end deep sequencing to analyze 532 protein and phosphoinositide kinases in 14 GC cell lines. We identified 10,604 single-nucleotide variants (SNV) in kinase exons including greater than 300 novel nonsynonymous SNVs. Family-wise analysis of the nonsynonymous SNVs revealed a significant enrichment in mitogen-activated protein kinase (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 48 publications
6
71
0
1
Order By: Relevance
“…Interestingly, recent evidence showed that STK31 was also found to be expressed abundantly in colorectal cancer and gastric and esophageal cancer, and thus suggested to be a novel cancer/testis (CT) antigen (Yokoe et al 2008;Zang et al 2011), indicating the acquisition of a gametogenic program in cancer involved in tumorigenesis. It is also noticeable that we did not explore the expression of STK31 during mice prenatal development.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent evidence showed that STK31 was also found to be expressed abundantly in colorectal cancer and gastric and esophageal cancer, and thus suggested to be a novel cancer/testis (CT) antigen (Yokoe et al 2008;Zang et al 2011), indicating the acquisition of a gametogenic program in cancer involved in tumorigenesis. It is also noticeable that we did not explore the expression of STK31 during mice prenatal development.…”
Section: Discussionmentioning
confidence: 99%
“…In the preclinical analysis included in the study, the growth of two patientderived tumor cell lines harboring MET exon 14 deletion (one from gastric and one from colon cancer) were strongly inhibited by both Met TKI and an anti-Met monoclonal antibody (29). Furthermore, two independent preclinical studies reported the presence of MET exon 14 deletion in gastric cancer cell lines (58,59). In particular, a genomewide analysis of 34 gastric cancer cell lines showed that only one cell line (Hs746T) has a splice site mutation of MET exon 14, concurrent with MET amplification and protein overexpression (58).…”
Section: Gastrointestinal Cancermentioning
confidence: 99%
“…Mutations of the Src-like kinase Brk (breast tumor kinase) have been identified at low frequency in different cancers as clear cell renal cell carcinoma [90], gastric cancer [91], head and neck squamous cell carcinoma [92], cutaneous squamous cell carcinoma [93] and pancreatic cancer [94]. The L16F mutant, situated in the SH3 domain, the R131L mutant, located in the SH2 domain, the L343F mutants in the kinase domain and the P450L mutant, located adjacent to the inhibitory tyrosine residue at the C-terminal tail of Brk, have been shown to be able to constitutively activate Brk [95].…”
Section: Constitutive Active Jak/stat Pathway In Other Tumorsmentioning
confidence: 99%